Capacitación jurídica en la empresa privada en Ibarra y su mejoramiento en la productividad - Bolaños Gualacata, Kevin Andres (2025)
This article addresses the relevance and impact of legal training in labor law in the business context, with a specific focus on a private company. Legal training covers key topics such as workers' rights and obligations, the structure and content of employment contracts, the various forms of contract termination, and creating a healthy and legally compliant work environment. It is proposed that adequate training in these areas is crucial to avoid misunderstandings, conflicts and potential litigation, while improving the relationship between employers and employees. Workers who understand their rights and responsibilities are better equipped to fulfill their obligations and advocate for their interests in an informed manner. For their part, employers who invest in legal training for their staff achieve not only regulatory compliance, but also greater employee satisfaction and retention, as well as a reduction in costs associated with legal disputes. The article also comparatively reviews various research studies that have evaluated the effectiveness of these training programs. Studies show that companies that implement continuous and specific training programs, adapted to the needs and particularities of the sector and its workforce, see an improvement in organizational cohesion and a decrease in work incidents.